Aeroacoustic simulation of rotorcraft propulsion systems. - Vouros, Stavros (Cranfield University, 2019)
Rotorcraft constitute air vehicles with unique capabilities, including vertical take- off and landing, hover and forward/backward/lateral flight. The efficiency of rotorcraft operations is expected to improve rapidly, due to the incorporation of novel technologies into current designs. Moreover, enhanced or even new capabilities are anticipated after the introduction of advanced fast rotorcraft configurations into the future fleet. The forecast growth in rotorcraft operations is essentially associated with an expected increase in adverse environmental impact. With respect to the forthcoming rotorcraft aviation advancements, regulatory and advisory bodies, as well as communities, have focused their attention on reducing pollutant emissions and acoustic impact of rotorcraft activity. Consequently, robust and computationally efficient noise modelling approaches are deemed as prerequisites towards quantifying the acoustic impact of present and future rotorcraft activity. Ultimately, these approaches need to cater for unique operational conditions encompassed by modern rotorcraft across designated flight procedures. Additionally, individual variations of key design variables need to be resolved, in the context of design or operational optimisation, targeted at noise mitigation. This work elaborates on the development and application of a robust and computationally efficient methodology for the aeroacoustic simulation of rotorcraft propulsion systems. A series of fundamental modelling methods is developed for the prediction of helicopter rotor noise at fully-integrated operational level. An extensive validation is carried out against existing experimental data with respect to prediction of challenging aeroacoustic phenomena arising from complex aerodynamic interactions. The robustness of the deployed method is confirmed through a cost-effective uncertainty analysis method focused on aerodynamic sources of uncertainty. A set of generalised modelling guidelines is devised for the case of not available input parameters to calibrate the aerodynamic models. The aspect of multi-disciplinary optimisation of rotorcraft at aircraft level in terms of maximising the potential benefits of novel technologies is also tackled within this work. A holistic schedule of optimal active rotor morphing control is derived, offering simultaneous mitigation of pollutant emissions and acoustic impact across a wide range of the helicopter flight envelope. Finally, the developed noise prediction method is incorporated into an operational-level optimisation algorithm, demonstrating the potential of active rotor morphing with respect to reduction of ground-noise impact. The contribution to knowledge arising from the successful completion of this work comprises both the development of methodologies for helicopter aeroacoustic analysis and the derivation of guidelines and best practices for morphing rotor control. Specifically, a generic operational-level simulation approach is developed which effectively advances the state-of-the-art in mission noise prediction. New insight is provided with respect to the impact of wake aerodynamic modelling uncertainty on the robustness of noise predictions. Moreover, the aeroacoustic aspects of a novel morphing rotor concept are explored and quantifications with respect to the trade-off between environmental and noise disciplines are offered. Finally, a generalised set of optimal rotor control guidelines is derived towards achieving the challenging environmental goals set for a sustainable future rotorcraft aviation.
Keywords: key design variables; design; operational optimisation; noise mitigation; rotor noise; aerodynamic interactions; uncertainty analysis